2011
DOI: 10.1089/dia.2010.0160
|View full text |Cite
|
Sign up to set email alerts
|

Associations Between Health Literacy, Diabetes Knowledge, Self-Care Behaviors, and Glycemic Control in a Low Income Population with Type 2 Diabetes

Abstract: Objective: This study assessed associations among health literacy, diabetes knowledge, self-care, and glycemic control in a low income, predominately minority population with type 2 diabetes. Methods: One hundred twenty-five adults with diabetes were recruited from a primary care clinic. Subjects completed validated surveys to measure health literacy, diabetes knowledge, and self-care (medication adherence, diet, exercise, blood sugar testing, and foot care). Hemoglobin A1c values were extracted from the medic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

21
236
3
17

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 245 publications
(277 citation statements)
references
References 43 publications
21
236
3
17
Order By: Relevance
“…Diabetes self-management strategies increase lifestyle adjustments to maintain best possible diabetes management to achieve optimal glycaemic control in type 2 diabetics [83][84][85][86][87][88][89][90][91]. In this study the current situation of adherence to self-care behaviour of type 2 diabetics in Arba Minch General Hospital and factors that contribute to efficient adherence to self-care behaviour of diabetics was investigated.…”
Section: Discussionmentioning
confidence: 99%
“…Diabetes self-management strategies increase lifestyle adjustments to maintain best possible diabetes management to achieve optimal glycaemic control in type 2 diabetics [83][84][85][86][87][88][89][90][91]. In this study the current situation of adherence to self-care behaviour of type 2 diabetics in Arba Minch General Hospital and factors that contribute to efficient adherence to self-care behaviour of diabetics was investigated.…”
Section: Discussionmentioning
confidence: 99%
“…The finding is similar to the findings of other authors who found that there was no correlation between knowledge [35] and attitude [36] with glycemic control. However, other studies [37][38][39] found that diabetes knowledge, attitude and adherence to health regimens were associated with glycemic control. Lack of relationships among age and gender and poor glycemic control in our study is consistent with Shani et al [40] who found neither age nor gender were related to the achievement of good glycemic control.…”
Section: Hba1c <7mentioning
confidence: 98%
“…Low HL has been associated with poor health outcomes for many diseases, especially chronic diseases such as diabetes (Berkman, Sheridan, Donahue, Halpern and Crotty, 2011;Martin, Williams, Haskard and DiMatteo, 2005;Sabaté, 2003;Van den Broucke, 2014). Several studies have shown that compared to patients with adequate HL, diabetic patients with low HL have poorer knowledge about their disease and its management (Bains and Egede, 2011;Fransen, von Wagner and Essink-Bot, 2012;Gazmararian, Williams, Peel and Baker, 2003;Powell, Hill and Clancy, 2007;van der Heide et al, 2014), adopt fewer self-management behaviours (Lai, Ishikawa, Kiuchi, Mooppil and Griva, 2013;van der Heide et al, 2014), and have poorer levels of glycaemic control and an increased risk of complications (Schillinger et al, 2002;van der Heide et al, 2014).…”
mentioning
confidence: 99%